2000
DOI: 10.1016/s0002-9440(10)64786-4
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Angiopoietin-1, Angiopoietin-2, and Tie Receptors after Middle Cerebral Artery Occlusion in the Rat

Abstract: Experimental models and studies on stroke patients have shown that hypoxia/ischemia induces vascular proliferation in the peri-infarct area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
141
0
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(157 citation statements)
references
References 41 publications
15
141
0
1
Order By: Relevance
“…The abrupt up-regulation of Ang-2 mRNA during non-neoplastic cerebral angiogenesis has been described previously in human arteriovenous malformations (Hashimoto et al, 2001), after systemic hypoxia in rat brain (Mandriota et al, 2000), and in infarcts produced by middle cerebral artery occlusion in the rat (Beck et al, 2000). Unlike the present study, Ang-1 mRNA levels in these models were similar or only slightly increased compared with control brains.…”
Section: Ang-1 and Ang-2 Expression During Cerebral Angiogenesissupporting
confidence: 58%
See 1 more Smart Citation
“…The abrupt up-regulation of Ang-2 mRNA during non-neoplastic cerebral angiogenesis has been described previously in human arteriovenous malformations (Hashimoto et al, 2001), after systemic hypoxia in rat brain (Mandriota et al, 2000), and in infarcts produced by middle cerebral artery occlusion in the rat (Beck et al, 2000). Unlike the present study, Ang-1 mRNA levels in these models were similar or only slightly increased compared with control brains.…”
Section: Ang-1 and Ang-2 Expression During Cerebral Angiogenesissupporting
confidence: 58%
“…Ang-1 and Ang-2 mRNA were localized in neurons, whereas Ang-1 was also observed in vessels (Stratmann et al, 1998). Subsequent studies reported only Ang-1 mRNA in glia and cerebellar Purkinje cells (Beck et al, 2000;Hashimoto et al, 2001) but not in blood vessels, whereas another study failed to demonstrate Ang-1 or Ang-2 mRNA in normal brain (Zagzag et al, 1999). These inconsistent results may be a result of technical difficulties such as fixation techniques and probe sensitivity.…”
Section: Ang-1 Ang-2 and Tie-2 Mrna Expression In Normal Brainmentioning
confidence: 99%
“…It is quite possible that the effect of Ang2 depends on differences in the VEGF levels (Goede et al, 1998;Holash et al, 1999;Beck et al, 2000). Our data provide evidence of a complementary Membrane fractions were collected 72 h after transfection and analysed by western blotting for Tie2 protein levels as described previously (Lee et al, 2006b).…”
mentioning
confidence: 57%
“…Several studies have shown that this contextual behavior of Ang2 is, at least partially, dependent on VEGF levels. Ang2 appears to initiate and stimulate angiogenesis when acting together with VEGF, but to induce vessel regression in the absence of VEGF (Goede et al, 1998;Holash et al, 1999;Beck et al, 2000). Such a coordinated effect implies the existence of certain mechanisms that both temporally and spatially govern the expression of these molecules and hence their concurrent or sequential effect on tumorigenesis.…”
mentioning
confidence: 99%
“…Using cDNA analysis, Hayashi et al [59] examined the expression levels of 96 angiogenesis-related genes after transient MCAO (tMCAO) in mice, and found that 42, 29, and 13 genes are upregulated at 1 h, 1 day, and 21 days, respectively, after transient occlusion. Beck et al [60] found that the mRNA expression of angiogenin-2, which promotes angiogenesis, is upregulated after 6 h of occlusion in MCAO rats. These changes lead to the synthesis of pro-angiogenic proteins such as VEGF.…”
Section: Angiogenesis After Cerebral Ischemiamentioning
confidence: 99%